2022
DOI: 10.1007/s42729-022-00938-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ZnO Particle Size and Soil Characteristics on the Estimation of Long-Term Zn Bioavailability by Chemical Extraction Methods and Diffusive Gradients in Thin-Films (DGT)

Abstract: The aim of this paper is to explore whether the long-term bioavailability of Zn in different soils can be predicted using operational extraction procedures. Green peas and beetroot were grown in two soils with contrasting physicochemical characteristics. Two Zn sources of different sizes (ZnO-nano or ZnO-bulk) were applied 1 year earlier, at different Zn application rates. The amounts of available Zn were assessed using the diffusive gradients in thin films (DGT) technique and different chemical extraction pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The Pearson correlation coefficients ( r ) between log-transformed values of Zn concentrations in crop and C DGT ranged between 0.787 and 0.915. Later, the same group of research reported C DGT for Zn well correlated with Zn accumulated by beetroot and green pea, with Pearson correlation coefficients between log-transformed values of the Zn concentrations in crops and C DGT in the range 0.78–0.96 (Almendros et al 2022 ).…”
Section: Dgt Applications For Heavy Metal Labile Fractions In Soilmentioning
confidence: 96%
“…The Pearson correlation coefficients ( r ) between log-transformed values of Zn concentrations in crop and C DGT ranged between 0.787 and 0.915. Later, the same group of research reported C DGT for Zn well correlated with Zn accumulated by beetroot and green pea, with Pearson correlation coefficients between log-transformed values of the Zn concentrations in crops and C DGT in the range 0.78–0.96 (Almendros et al 2022 ).…”
Section: Dgt Applications For Heavy Metal Labile Fractions In Soilmentioning
confidence: 96%